Marketing Strategy of Tomato’s Trader at Pasar Kasih, Kota Kupang, Nusa Tenggara Timur - Aldi F Taimenas; Maximilian M. J. Kapa; Lika Bernadina (Buletin Ilmiah Impas, 2022)
This study was held at the Kasih market Kupang in December 2019 to January 2020. With the aim to know the marketing mix, revenue and marketing strategy of tomato commodity traders the Kasih market City of Kupang. Kasih market Kupang was selected purposively as the location of research with consideration that this market is strategically located in the middle of Kupang City. The population in this study is all tomato traders who have been trading for more than two years. Sampling techniques used snowball sampling techniques, and as many us 30 sample traders have been interviewed to obtime the primary data. Data was analyzed according with the research objectives namely marketing mix analysis, revenue analysis and SWOT analysis. The result showed that; 1). Marketing Mix in Kasih market is: Product strategy, Price, Promotion and Place, show that traders apply quality improvement, characteristic of product, positioning product throungh price to consumer and production farmers, trader use direct promotion to the consumer, because the strategic location for traders and consumers. 2). The average income obtained by the tomato commodity trader for one month Rp. 8.374.833,00. 3). Analisys of the internal and external factors (IFAS/EFAS) that influence on the strategy of tomato traders in Kasih market generate a total score of IFAS of 3.00 which means strong internal positions. While the total EFAS score is 2.53 which means the tomato traders in the Kasih market Kupang are responding to existing opportunities and avoiding threats in the market.